A Wedding in Avondale B.3 - Boonstra, Jean; Nang Chan Yeema (Nampa, ID USA Pacific Press Publishing Association, 2004)
Heather's Aunt Rachel meets handsome Pastor Reid, and love begins to grow. But nice, polite Pastor Reid just happens to be Ethel's "Uncle John." That spells trouble. After a very important announcement "Aunt Rachel is getting married!" was made, a whirl of wedding preparations follows. As Heather delivers invitations, the voices she hears shock her. Why can't the future in-laws learn to love and accept sweet Aunt Rachel?
Keywords: Story Collection